Tutoring and Peer-tutoring : Roles and Responsibilities of Tutors and Peer-tutors - Bakhshiyeva, Sabina; Gasimzade, Nubar; Bakhshiyeva, Sabina; Mammadova, Zeynab (ADA University, 2020)
This exploratory qualitative study aimed to explore the roles and responsibilities of tutors and peer tutors at X University. More specifically, the research was oriented on gaining a better understanding of whether tutors and peer-tutors recognized their roles, knowledge, skills, competencies, and experiences while performing their roles and fulfilling their responsibilities. In addition, the study aimed at discovering tutees' perception of tutoring and peer-tutoring experiences. Qualitative interviews were conducted with two tutors, four peer tutors and four tutees from the Student Academic Support Services at X University. Besides, to collect comprehensive data, the Capstone team did observations during two tutorial sessions and a document review. Four main findings emerged from the data: the roles and responsibilities of tutors and peer tutors; tutors’ and peer tutors’ perceptions about their roles and responsibilities in peer-tutoring; and freshman’s perceptions of peer-tutoring. Hence, data analysis resulted in unforeseen findings, such as challenges associated with tutoring and peer tutoring. Based on the literature review and the data from this qualitative research study, recommendations for best practices to improve the experiences of tutoring and peer tutoring at X University were discussed in detail. Recommendations were accomplished by designing a new handbook for Student Academic Support Services.
Keywords: Education